Review of Chinese species of genus Xenovarta Viraktamath (Hemiptera: Cicadellidae: Deltocephalinae: Scaphytopiini) with description of a new species - Duan, Yani; Zhang, Yalin (Zootaxa, 2010)
The Chinese leafhopper species of the genus Xenovarta Viraktamath are reviewed, one new species Xenovarta longicornis sp. n. is described and a key is provided for the six Oriental species of the genus.